Pengembangan Subject Specific Pedagogy (SSP) pada Pembelajaran Tematik Terpadu dalam Mengimplementasikan Kurikulum 2013 Sekolah Dasar - Deni Moh. Budiman (Jurnal Edukasi Sebelas April, 2020)
This research is a study of differences in curriculum development in 2013 which aims to determine the results of developing subject-specific pedagogy (SSP) in integrated thematic learning for elementary school teachers in the Cicalengka sub-district. The procedure for this research method uses the Mixed Method, which is a combination of quantitative and qualitative methods in a study. Mixed-Method (combined method: qualitative-quantitative) is a method using a combination of research procedures, where one method is more dominant than another method. The less dominant method is only positioned as a complementary method as additional data. The more dominant method in this research is the qualitative method and a complementary method is a quantitative method. Data using sequential explanatory research model and data obtained through field research (Filed Research). In analyzing the data, the writer uses the Mean (average) formula and the last is formulated using the CNS development ability category. From the research conducted at two different elementary schools in the Cicalengka sub-district, namely public elementary schools and private elementary schools, the results showed that the development of subject-specific pedagogy (SSP) in integrated thematic learning in implementing the 2013 curriculum for elementary schools in Cicalengka sub-district was very good.